Communicative and Leadership Competences of a Patrol Police Officer as Factors of Forming His Readiness for Professional Activity - Valentyna Tyurina; Liudmyla Romanyshyna (Pedagogical Discourse, 2025)
The article substantiates the relevance of the problem of forming and developing  communicative and leadership competencies of future patrol police officers. The definitions of the concepts of «competence», «communicative competence» and «leadership competence» are given. It is concluded that the process of forming leadership and communicative competences is directly related to the acquisition of skills and abilities that ensure the competent performance of leadership and communicative functions. The formation of communicative and leadership competencies as professionally significant qualities of a future patrol police officer requires not only the acquisition of certain knowledge, skills and abilities, but also certain personal qualities as components of these competencies. The formation of skills, abilities and value orientations is facilitated by cadets performing special tasks and exercises that are similar in content and conditions to real-life situations. One of the effective and promising methods for developing skills, abilities and personal qualities is training and classes with training elements. In general, the training of future patrol police officers at the Higher Education Institutions of the Ministry of Internal Affairs of Ukraine, in order to develop their leadership and communication competencies as components of their readiness for professional activity, should be aimed at developing the following abilities, skills and habits: active listening; overcoming potential language barriers; asking open questions;  understanding body language and non-verbal signals; not taking insults or verbal attacks personally; understanding the limits of verbal de-escalation; effective and consistent communication; crisis communication; proactivity skills; focus on self-education and self-improvement in the field of leadership and communication. The results of an experimental study on the formation of communication and leadership competencies in future patrol police officers during their professional training are presented. A statistically significant positive trend was found in most indicators in the groups after studying a special course, writing term papers and creative works, and participating in training.